Impact of the COVID-19 pandemic on anesthesiologists in India: A cross-sectional online survey of the practices, preparedness, and mind-set - Gauri Raman Gangakhedkar; Sohan Lal Solanki (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: India is one of the five worst hit countries in the world due to COVID-19, by the fourth week of June 2020. The impact of COVID-19 on the health practices is well-documented but there are no studies assessing its impact on anesthesiologists in India. This study aims at assessment of the impact of COVID-19 on the practices followed, the preparedness, and mindset of anesthesiologists in India. Material and Methods: Using Google forms, a cross-sectional, questionnaire-based survey was conducted between the 5th and 22nd of May, 2020, among trainees and practicing anesthesiologists, in India. The anesthesiologists were invited to participate, using their e-mail addresses and through the social media platforms such as Facebook and WhatsApp. The responses that were generated, were analyzed using SPSS version 23 (IBM, Armonk, NY). Results: Of the 707 anesthesiologists who participated, 68.3% had already worked in a COVID-19 specialty unit. Only 41.7% of the anesthesiologists felt confident that they had sufficient knowledge to deal with COVID-19 infected patients. Fear of catching the infection and infecting loved ones were important causes of anxiety, which was seen in 95% of the participants. Majority of the participants, (64.5%) did not think that elective surgical procedures could be restarted at this point. Conclusion: COVID-19 has had grave impact on anesthesiologists, on the professional and personal front, and will possibly cause near-permanent changes in the work culture. Restarting elective surgical procedures, will require meticulous planning. In spite of their self-perceived under-preparedness to combat COVID-19, an overwhelming majority of participating anesthesiologists were prepared to contribute to the management of COVID-19.